Mary Spotswood correspondence - Spotswood, Mary.
ALS (undated; New Post, Va.?) from Spotswood to Anna Maria Dandridge Bassett, sister of Martha Washington, acknowledging their friendship.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bassett, Anna Maria Dandridge, -- -1777 -- Correspondence; Washington, Martha, -- 1731-1802 -- Family; Virginia -- Social life and customs -- To 1775.